The methodology of scientific research programmes - Lakatos, Imre 1922-1974 (Cambridge University Press, 1978)
Imre Lakatos' philosophical and scientific papers are published here in two volumes. Volume I brings together his very influential but scattered papers on the philosophy of the physical sciences, and includes one important unpublished essay on the effect of Newton's scientific achievement. Volume II presents his work on the philosophy of mathematics (much of it unpublished), together with some critical essays on contemporary philosophers of science and some famous polemical writings on political and educational issues. Imre Lakatos had an influence out of all proportion to the length of his philosophical career. This collection exhibits and confirms the originality, range and the essential unity of his work. It demonstrates too the force and spirit he brought to every issue with which he engaged, from his most abstract mathematical work to his passionate 'Letter to the director of the LSE'. Lakatos' ideas are now the focus of widespread and increasing interest, and these volumes should make possible for the first time their study as a whole and their proper assessment
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte; Naturwissenschaft; Philosophie; Science / Methodology; Science / History; Science / Philosophy; Wissenschaftstheorie; Forschungsprogramm; Methodologie; Aufsatzsammlung